Bilateral thalamic glioma in a 6-year-old child - Rajput, Dinesh K. (Medknow Publications, 2010)
Bithalamic gliomas are extremely rare tumors of central nervous system. Although they are usually benign in nature, their outcome is poor because of the involvement of thalamic nuclei and inadequate surgical excision. Surgery is usually done to get tissue for diagnosis. Role of radiotherapy and chemotherapy is questionable. They are unique in their metabolic and neuroradiological properties. We report herein a 6-year-old male of bithalamic astrocytoma (WHO grade 2) who presented with raised intracranial pressure and tremors in right upper limb. The child had a very huge bithalamic mass which was debulked through the interhemispheric transcallosal approach in order to reduce the mass effect. He had a stormy post-operative course to recover gradually.